2016
DOI: 10.1002/2016tc004177
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Neoproterozoic (ca. 830-800 Ma) metamorphicP-Tpaths link Tarim to the circum-Rodinia subduction-accretion system

Abstract: Long‐lived exterior accretionary orogeny shapes tectonothermal evolution of the peripheral building blocks of supercontinents and leads to considerable crustal growth. However, such accretionary orogeny has only been locally recognized for the Rodinia supercontinent. Here a suite of newly discovered mid‐Neoproterozoic high‐grade metamorphic rocks in the northern Tarim Craton, NW China, are used to test the exterior accretion hypothesis for Rodinia. These rocks occur as dark‐colored mafic and calc‐silicate boud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 103 publications
(209 reference statements)
1
23
0
Order By: Relevance
“…The Latest Mesoproterozoic and Neoproterozoic tectonic evolution of the Tarim Craton, as well as that of other areas of the northern Xinjiang, was correlated to the assembly and break‐up of the supercontinent Rodinia (e.g., Cawood et al, ; Evans, ; J. Gao et al, ; Ge, Zhu, Wilde, He, et al, ; Ge et al, ; Z. X. Li, Evans, & Halverson, ; Z. Q. Xu et al, ; C. L. Zhang, Zou, et al, ; W. B. Zhu et al, ). Our new results and previous data reveal five pulses of Neoproterozoic magmatism: 995 to 901 Ma (peaked at ~956 Ma), 886 to 752 Ma (peaked at ~823 Ma), 736 to 694 Ma (peaked at ~704 Ma), and 665 to 610 Ma (peaked at ~638 Ma).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Latest Mesoproterozoic and Neoproterozoic tectonic evolution of the Tarim Craton, as well as that of other areas of the northern Xinjiang, was correlated to the assembly and break‐up of the supercontinent Rodinia (e.g., Cawood et al, ; Evans, ; J. Gao et al, ; Ge, Zhu, Wilde, He, et al, ; Ge et al, ; Z. X. Li, Evans, & Halverson, ; Z. Q. Xu et al, ; C. L. Zhang, Zou, et al, ; W. B. Zhu et al, ). Our new results and previous data reveal five pulses of Neoproterozoic magmatism: 995 to 901 Ma (peaked at ~956 Ma), 886 to 752 Ma (peaked at ~823 Ma), 736 to 694 Ma (peaked at ~704 Ma), and 665 to 610 Ma (peaked at ~638 Ma).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of a large number of investigations, several fundamental aspects of the geology and tectonics of the Tarim Craton and south‐western CAOB remain controversial. For instance, in terms of the mechanism and timescale of the rifting processes in the Tarim Craton during the break‐up of the Neoproterozoic supercontinent Rodinia, opinions are diverse and include the superplume‐model (X. P. Long, Yuan, Sun, Kröner, et al, ; Z. Q. Xu et al, ; C. L. Zhang, Zou, Li, Wang, ) and back‐arc extension model (Ge, Zhu, Wilde, He, et al, ; Ge, Zhu, & Wilde, ). Furthermore, the origin, timescale, and subduction polarity of the Palaeozoic South Tianshan Ocean that existed between the Palaeozoic Tarim and SW CAOB also remain debated.…”
Section: Introductionmentioning
confidence: 99%
“…The microcontinents (such as the CTB, KYB, KNTS) in the western CAOB and the Tarim Craton were interpreted to have been incorporated into the periphery of Rodinia through long‐lived subduction‐accretion processes, as evidenced by widespread late Mesoproterozoic to early Neoproterozoic magmatic rocks, and the ~830–790‐Ma Aksu blueschists and HP granulites (Ge, Zhu, Wilde, He, et al, ; Ge et al, ; He et al, ; Kröner et al, , ; Wang, Liu, et al, ). It was further suggested that these microcontinents and the Tarim Craton were detached from peri‐Rodinia by back‐arc rifting or plume‐related breakup (e.g., Gao et al, ; Ge, Zhu, Wilde, He, et al, ; Ge, Zhu, Zheng, et al, ; Zhang, Li, et al, ), leading to the opening of multiple oceanic basins, such as the proto‐Tethys Ocean between the Tarim Craton and northwest Australia (Zhang et al, ), and the South Tianshan, Terskey, and Djalair‐Naiman oceanic basins as the southern branches of the Paleo‐Asian Ocean (Figure ; Gao et al, ; Ge, Zhu, Wilde, He, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Paleozoic strata consist of Cambrian–Ordovician phosphorous siliciclastic and carbonate sequences, Silurian–Devonian shallow‐marine clastic sediments, and Carboniferous–Permian clastic‐carbonates and volcanic beds, which are separated by two major angular unconformities (Carroll et al, ; Han et al, ; Xiao et al, ). Several magmatic and tectonothermal events display Neoarchean to Permian ages, including ~830–790 Ma HP granulite‐facies metamorphism (Ge et al, ; He et al, ), ~780–760 Ma Aksu blueschist‐facies metamorphism (Yong et al, ; Zhang et al, ), and ~460–380 Ma arc‐related plutonic rocks (Ge, Zhu, Wu, et al, ; Ge, Zhu, Wilde, He, et al, ).…”
Section: Geological Settingmentioning
confidence: 99%
“…The response time of the assembly and breakup was variable in different parts of Rodinia, but the Rodinia supercontinent was assembled at ~1.1–1.0 Ga and fragmented at ~0.8–0.7 Ga totally (Rogers & Santosh, ). The Tarim Craton has been broadly accepted to be involved with the assembly and breakup of the Neoproterozoic Rodinia supercontinent (Ge et al, ; Ge, Zhu, & Wilde, ; He, Zhang, Zong, Wang, & Yu, ; Li, Qiu, Chang, & Yang, ; Lu et al, ; Shu, Deng, Zhu, Ma, & Xiao, ; Zhang, Zou, Li, & Wang, ), and the most significant peak age of ~0.8 Ga in the magmatic records of the Tarim Craton is probably associated with the Rodinia supercontinent cycle (Zhang et al, ). This Grenville event (~1.1–0.85 Ga) in the Tarim Craton makes it different from the North China Craton (Lu et al, ; Ma, Shu, Santosh, & Li, ; Rojas‐Agramonte et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%